Potential Role of Bromelain in Wound Healing Application: A Review - Ng, Celine; Hamzah, Mohd Syahir Anwar; Mat Nayan, Nadirul Hasraf (International Journal of Integrated Engineering, 2023)
Bromelain is a type of proteolytic enzymes that extracted from pineapple plant (Ananas comosus). Fruit and stem bromelain can be extracted from pineapple stem and fruit respectively. It can also being obtained from pineapple wastes such as core, crown and peel. Various extraction and purification method such as reverse micellar system, aqueous two-phase system, chromatographic techniques and membrane filtration had been employed to produce high quality bromelain. Bromelain had been clinically known since 1876 and introduced as therapeutic compound in 1957. Due to its safety and showed undesired side effects, bromelain has earned growing acceptance and compliance among patients as phytotherapeutical drug. Bromelain is regarded as one of the nutrient support for wound healing as it contains various closely related proteinases demonstrating anti-inflammatory, fibrinolytic and debridement effects.